Fundamentals of advanced accounting - Hoyle, Joe Ben (McGraw - Hill Irwin, 2011)
Fundamentals of Advanced Accounting, 2/e is ideal for those schools wanting to cover 12 chapters in their advanced accounting course. Typically, this course covers 5-6 consolidations chapters, two foreign currency chapters, two partnership chapters, and 2-3 governmental and not-for-profit chapters. Fundamentals of Advanced Accounting boasts the same great assets that have made the authors' longer Advanced Accounting a success, including the incorporation of the latest FASB pronouncements, the integration of skill preparation for the new CPA exam, and of course, great authorship